Principles and Practice of Lacrimal Surgery (Springer Singapore, 2018)
This second edition of the highly successful and comprehensive text on lacrimal disorders presents the latest developments in this rapidly evolving field. The new edition includes six new chapters, additional photographs and all chapters now have a separate section on recent advances. Written by experts in the field of dacryology, this book is a practical guide to evaluating and managing patients with lacrimal disorders. It methodically discusses basic anatomy and underlying pathology, patient evaluation, and all surgical procedures currently used to manage such disorders. It thoroughly yet concisely reviews surgical modalities including the endoscopic and micro-endoscopic approaches and provides ample illustrations for a better understanding. Since familiarity with a surgical technique is incomplete without the knowledge of risk factors and red flags, the text highlights ways of dealing with surgical complications and failure. Further it discusses in detail controversial topics and treatment dilemmas and reviews the current consensus among the experts. This is an up-to-date reference work for dacryologists, oculoplastic surgeons, general ophthalmologists as well as fellows in training.